Relationships between diameter growth and functional wood anatomy in Eucalyptus globulus clones - Monteoliva, Silvia-Estela; Sallesses, Leonardo; Quiñones-Martorello, Adriana; Moreno, Karen; Gyenge, Javier; Fernández, Maria-Elena (Forest Systems, 2024)
Aim of study: We aimed to 1) analyze the variability of wood hydraulic anatomical traits in 10 clones of E. globulus Labill. with different growth rates, and 2) determine whether the magnitude of diameter growth affects the relationships between anatomical variables and diameter at breast height (DBH).Area of study: 25-year-old common garden trial in Balcarce, Buenos Aires, Argentina.Material and methods: We measured vessel diameter and number per unit area in transverse histological sections of stem wood, and calculated the proportion of vessel lumens, vessel composition (S), and theoretical specific hydraulic conductivity (Ks) of 10 E. globulus clones of high (HG) and low (LG) mean growth rates (measured as DBH) under field conditions.Main results: There was a difference in the range of variability in hydraulic anatomy between HG and LG clones, with LG clones showing a wider range. HG clones had wood with larger and fewer vessels and higher S compared to LG clones, with similar Ks between both growth groups. No clear or strong trends were observed between wood anatomy and DBH within the HG and LG groups, but across all clones a high correlation (Spearman coefficient r; p<0.001) was observed between vessel number ‒ DBH (r= -0.68), and S ‒ DBH (r= 0.74). These correlations were driven by contrasting mean values of both growth groups.Research highlights: Commercial E. globulus clones present a relatively large variation in anatomical and hydraulic strategies. However, in contrast to what is postulated for various woody species, there was no clear relationship between theoretical hydraulic efficiency and individual diameter growth rate in the genotypes studied.